Analisis Penerimaan Teknologi Artificial Intelligence dalam Penyelesaian Tugas Mahasiswa Menggunakan Model Tam: Studi Kasus Mahasiswa di Wilayah Banyumas - Wisnu Mu’amar; Andri Firmansyah Caniago; Fadil Tazakka Pribadi; Arifah Budi Hidayah; Ito Setiawan (Lembaga Pengembangan Kinerja Dosen, 2025)
The development of Artificial Intelligence (AI) technology has a significant impact in the world of education, including supporting the completion of student academic tasks. This study aims to analyze the level of acceptance of students in the Banyumas area towards the use of AI technology in academic activities. The research used a quantitative approach with a survey method of 150 students from various universities in Banyumas. The questionnaire instrument was developed based on the Technology Acceptance Model (TAM) framework, which includes three main variables: perceived ease of use, perceived usefulness, and behavioral intention. The analysis was conducted using SPSS through validity, reliability, Pearson correlation, and multiple linear regression tests. The results showed that perceived ease of use and usefulness had a significant effect on students' intention to use AI technology. Students feel that this technology is easily accessible and useful in supporting task completion and material understanding. These findings strengthen the validity of the TAM model in the academic context. This study provides implications for technology developers to improve user experience, as well as for educational institutions to more actively encourage the use of AI technology in learning.